Serial imaging after pulmonary embolism and correlation with functional limitation at 12 months: Results of the ELOPE Study. Issue 4 (17th June 2018) - Ma, Kim A.; Kahn, Susan R.; Akaberi, Arash; Dennie, Carole; Rush, Christopher; Granton, John T.; Anderson, David; Wells, Philip S.; Rodger, Marc A.; Solymoss, Susan; Kovacs, Michael J.; Rudski, Lawrence; et al.
Abstract: Essentials Exercise Limitation 1 year after an acute pulmonary embolism is common. Serial imaging after acute pulmonary embolism is not well described and how it affects exercise limitation remains unknown. 1 year after an acute pulmonary embolism chronic changes are common, more so on perfusion lung scanning than CT pulmonary angiography, but imaging findings did not predict exercise limitation. Introduction: Risk factors for exercise limitation after acute pulmonary embolism (PE) are unknown. As a planned sub‐study of the prospective, multicenter ELOPE (Evaluation of Long‐term Outcomes after PE) Study, we aimed to describe the results of serial imaging by computed tomography pulmonary angiography (CTPA) and perfusion scan during 1 year after a first episode of acute pulmonary embolism, and to assess the association between imaging parameters and exercise limitation at 1 year. Methods: In a prospective cohort study, 100 patients were recruited between June 2010 and February 2013 at five Canadian university–affiliated hospitals. CT pulmonary angiography was performed at baseline and 12 months, perfusion scan at 6 and 12 months, and cardio‐pulmonary exercise testing at 1 and 12 months. Imaging parameters included: on CT pulmonary angiography, CT obstruction index (CTO) (% clot burden in the pulmonary vasculature), and on perfusion scan, pulmonary vascular obstruction (PVO) (% perfusion defect). Abnormal cardio‐pulmonary exercise test (primary outcome) was defined as percent of predicted peak oxygen uptake (VO2) <80%. Results: Mean (median; SD) CT obstruction index was 28.1% (27.5%; 18.3%) at baseline, 1.2% (0%; 4.3%) at 12 months. Mean (median; SD) pulmonary vascular obstruction was 6.0% (0%; 9.6%) at 6 months, 5.6% (0%; 9.8%) at 12 months. Eighty‐six patients had exercise testing at 12 months, and 46.5% had VO2 < 80% predicted. Mean (median; SD) CT obstruction index at 1 year was similar in patients with percent‐predicted VO2 peak <80% vs >80% on 1‐year cardio‐pulmonary exercise testing (1.4% [0%; 5.7%] vs 1.0% [0%; 2.4%]; P = .70). Mean (SD) pulmonary vascular obstruction at 6 and at 12 months was similar in patients with percent‐predicted VO2 peak <80% vs >80% (6 months: 5.9% [0%; 10.4%] vs 6.2% [4.5%; 9.0%]; P = .91; 12 months: 5.1% [0%; 10.2%] vs 6.0% [0%; 9.7%]; P = .71). Conclusions: Imaging findings after pulmonary embolism did not predict exercise limitation. Residual thrombus does not appear to explain long‐term functional limitation after pulmonary embolism.